Studi Kualitatif Manajemen Orangtua dalam Penggunaan Gadget dan Pengaruhnya terhadap Kemampuan Interaksi Sosial Anak Usia Dini - Syahida, Aruny Amalia; Daliman (Journal of Psychology and Treatment, 2022)
The use of gadgets in early childhood has a very large impact or influence on the achievement of the stages of child development. And parents must take preventive action or have rules for using gadgets, so that children are not exposed to the negative impacts of gadgets that can be an obstacle to their development, especially the development of social interactions. This study aims to explore the management or parental settings regarding the use of gadgets in early childhood and its effect on the ability of social interaction in children, using a qualitative descriptive research method. Collecting data using a questionnaire containing open-ended questions to 75 participants by proposive sampling. The data analysis technique used is Miles and Huberman interactive analysis. The results showed that there were 6 categories of parental gadget use management for their children, namely limiting the hours of gadget use; make a schedule for using gadgets; set up the gadget area; provide assistance to children; does not give full access; provide rewards and punishments. Based on this research, it can be concluded that of 75 participants, 92 percent have rules for using gadgets in their children, and 85% of their children's social interaction skills are good or not experiencing obstacles.